2019
DOI: 10.1097/jan.0000000000000288
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Student Drinking Behaviors at the Beginning of the First Academic Year at One University in Southern Italy

Abstract: It is well recognized that both college and noncollege students are at-risk age groups for alcohol consumption. We investigated the alcohol consumption habits of undergraduate students with an emphasis on binge drinking. Participants (N = 809, 61.2% female) were freshmen attending courses at one of the main universities of southern Italy. They were asked to fill out a paper-and-pencil questionnaire that was administered between October 2017 and January 2018. Nearly 90% of the questioned students reported drink… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…However, the behaviour is increasing among women (Andersson et al, 2013;Bartoli et al, 2014;Slutske, 2005;Young et al, 2005) and young people, even those below the legal drinking age (NIAAA, 2021). Some studies in Italy, mainly conducted on university students, show that this country is aligned with international trends on binge drinking among young adults (D'Alessio et al, 2006;De Salvia et al, 2019;Di Grande et al, 2000). Moreover, according to the Italian Ministry of Health (2019), 2.1% of consumers aged 18-24 engaged in "habitual excess consumption" (i.e.…”
Section: Introductionmentioning
confidence: 97%
“…However, the behaviour is increasing among women (Andersson et al, 2013;Bartoli et al, 2014;Slutske, 2005;Young et al, 2005) and young people, even those below the legal drinking age (NIAAA, 2021). Some studies in Italy, mainly conducted on university students, show that this country is aligned with international trends on binge drinking among young adults (D'Alessio et al, 2006;De Salvia et al, 2019;Di Grande et al, 2000). Moreover, according to the Italian Ministry of Health (2019), 2.1% of consumers aged 18-24 engaged in "habitual excess consumption" (i.e.…”
Section: Introductionmentioning
confidence: 97%
“…Apart from individual and environmental effects on substance abuse, use of tobacco and alcohol have been reported as risk factors for illegal drug consumption in higher education students in both cross-sectional and longitudinal studies [1,2,6,[31][32][33][34][35][36][37][38][39][40]. Tobacco smoking increases the risk of both illicit drug use (i.e., cannabis use, illegal drug use and other non-medical use of prescription drugs) [31][32][33] and alcohol abuse [31,34,35]. Students with risky alcohol behavior are more likely to show illegal drug abuse as well [36,37].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we found that certain health habits such as smoking tobacco and the intake of stimulant beverages increase the likelihood of substance use. Previous research has generally shown that tobacco use alone predicts both alcohol abuse and illicit drug use [109,110]. These results could be explained by the gateway hypothesis, which holds that the use of a legal and easily accessible harmful substance, such as tobacco, increases the risk of starting to use another, probably more harmful, drug [111].…”
Section: Discussionmentioning
confidence: 99%
“…A person who consumes alone tends to manifest negative affective traits and depressive symptoms to a greater extent [120]. The predictive model identified in our study has attempted to relate the social and personal consequences of substance use/abuse to some well-known sociodemographic and lifestyle variables, such as age, sex, smoking, stress level and depressive symptoms [94,100,103,104,109,110,114,[116][117][118]120], while others are new, e.g., living alone or with family or a friend, the presence of chronic disease, sedentary lifestyle and perceived health status. These warrant further research in order to establish health-promotion strategies and policies for individuals who are more vulnerable or present risk factors to the adverse personal and social consequences of drug abuse.…”
Section: Discussionmentioning
confidence: 99%